ANTI TUMOUR EFFECT OF AQUEOUS EXTRACT FROM HELIX ASPERSA - IBTISSEM EL OUAR; CORNELIA BRAICU; DALILA NAIMI; ALEXENDRU IRIMIE; IOANA BERINDAN-NEAGOE (International Journal of Pharma and Bio Sciences, 2013)
The garden snail Helix aspersa is a big land snail found widely in the Mediterranean countries; it has a high economic and nutritional value. The aim of this study is to investigate the anticancer activity of Helix aspersa extract against breast cancer cells Hs578T. Our assays showed that the extract had a high cytotoxicity against tumour cells; it acts by inducing necrosis and downregulating BcL2 expression. These results are novel and demonstrate that H. aspersa extract may serve as a source of a new anticancer drug or as an associated treatment in chemotherapy that inhibits BcL2 expression.